Secukinumab demonstrates superiority over narrow‐band ultraviolet B phototherapy in new‐onset moderate to severe plaque psoriasis patients: Week 52 results from the STEPIn study. (27th January 2023) - Iversen, Lars; Conrad, Curdin; Eidsmo, Liv; Costanzo, Antonio; Narbutt, Joanna; Pinter, Andreas; Kingo, Külli; Rivera Diaz, Raquel; Kolbinger, Frank; Nanna, ManikPrabhu; Frueh, Jennifer Annika; Jagiello, Piotr
Abstract: Background: Biologic treatments have been studied mainly in patients with a long‐term history of psoriasis and previous treatment failures. Objectives: The purpose of this primary analysis of the STEPIn study is to determine whether early intervention with secukinumab in patients with new‐onset moderate to severe plaque psoriasis is superior to standard of care treatment with narrow band ultraviolet B (nb‐UVB) phototherapy. Methods: The STEPIn study is a randomized, open‐label, multicentre study to investigate early intervention with 52 weeks of secukinumab 300 mg administered subcutaneously versus standard treatment with nb‐UVB phototherapy in patients with new‐onset (≤12 months) moderate to severe plaque psoriasis (NCT03020199). The primary and additional secondary endpoints were ≥90% improvement in Psoriasis Area and Severity Index (PASI 90) at Week 52 and Investigator's Global Assessment (IGA mod 2011) 0/1 response at Week 52, respectively. Results: In the secukinumab and nb‐UVB study arms, 77/80 and 76/80 randomized patients received at least one dose of study treatment, respectively. The primary endpoint was achieved: 91.1% (70/77) of patients achieved a PASI 90 response at Week 52 in the secukinumab arm versus 42.3% (32/76) in the nb‐UVB arm ( p  < 0.0001, odds ratio [OR] estimate [95% confidence intervals, CI] = 16.3 [5.6, 46.9]). The additional secondary endpoint was also achieved: 85.7% of patients achieved an IGA 0/1 response at Week 52 in the secukinumab arm versus 36.8% in the nb‐UVB arm ( p  < 0.0001). The safety data were consistent with the safety profiles of secukinumab and nb‐UVB with no new or unexpected safety signals. Conclusions: Secukinumab was superior to nb‐UVB in treating patients with new‐onset moderate to severe plaque psoriasis. The high and sustained skin clearance observed indicates that biologic treatment for psoriasis may be more effective if used early in the disease course.